Estudio de un modelo de optimización para un sistema de ruteo de vehículos con ventanas de tiempo (2020)
This article studies a case of transportation and routing of vehicles with time windows (VRPTW) in the city of Bogotá. The solution of this programming model seeks to ensure that the logistics chains of literary texts responsible for the distribution of literature in the city obtain a reduction in transportation costs, which represent a large part of the total logistics cost. In addition, it seeks to achieve compliance with all time windows imposed by customers, since compliance with requirements is currently highly valued by customers, taking into account, in addition, the different restrictions that may arise in a real environment .